2020
DOI: 10.1021/acs.jafc.0c04299
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Eicosapentaenoic Acid Production by Grafting a Heterologous Polyketide Synthase Pathway in the Thraustochytrid Aurantiochytrium

Abstract: Eicosapentaenoic acid (EPA) is an essential nutritional supplement for human health. The most prominent dietary source of EPA is fish oil, which is unsustainable because of the decline in fishery resources and serious environmental pollution. Alternatively, a heterologous polyketide synthase pathway for EPA biosynthesis was assembled in Thraustochytrid Aurantiochytrium. A 2A peptide-based facile assembly platform that can achieve multigene expression as a polycistron was first established. The platform was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…SK4 showed that the fatty acid content of the engineered strain was 44% higher than that of the wild type [ 11 ]. Furthermore, a recent study showed that the whole polyketide synthase (PKS) pathway from Shewanella japonica was expressed in Aurantiochytrium , resulting in a 26.9% increase in the lipid yield [ 12 ]. Up to date, nine genera of thraustochytrids have been recognized [ 13 ], however, efficient gene editing tools suitable for editing thraustochytrids have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…SK4 showed that the fatty acid content of the engineered strain was 44% higher than that of the wild type [ 11 ]. Furthermore, a recent study showed that the whole polyketide synthase (PKS) pathway from Shewanella japonica was expressed in Aurantiochytrium , resulting in a 26.9% increase in the lipid yield [ 12 ]. Up to date, nine genera of thraustochytrids have been recognized [ 13 ], however, efficient gene editing tools suitable for editing thraustochytrids have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang et al reported that Aurantiochytrium sp. transformed with a bacterial EPA-producing PUFA-S gene cluster produced 2.7 g/L EPA 42 . To date, the highest yield of EPA was achieved by engineered Yarrowia lipolytica , which was transformed with several heterologous genes that constitute the ELO/DES pathway required for EPA synthesis 43 .…”
Section: Discussionmentioning
confidence: 99%
“…ONC-T18 [ 55 ], and A. limacinum SR21 [ 52 ], while foot-and-mouth disease virus 2A (F2A) peptides have been used in Aurantiochytrium sp. SD116 [ 41 ]. In Aurantiochytrium sp.…”
Section: The Properties Of the Dna Related To Gene Expression In Thraustochytridsmentioning
confidence: 99%
“…In Aurantiochytrium sp. SD116, the proteins that contain F2A peptides were nearly 100% cleaved [ 41 ]. However, in Thraustochytrium sp.…”
Section: The Properties Of the Dna Related To Gene Expression In Thraustochytridsmentioning
confidence: 99%
See 1 more Smart Citation